Family centred care and family delivered care – What are we talking about?. Issue 1 (February 2018) - Banerjee, J.; Aloysius, A.; Platonos, K.; Deierl, A.
Abstract: Family centred care (FCC) is an integral part of high quality neonatal care in developed countries. More recently, family integrated care (FIC) is increasingly becoming a more popular model of care delivery in neonatal units. We strongly believe that FIC is the voice of the modern family in the neonatal unit and will provide significant benefit not only in terms of infant medical outcomes, but will also reduce stress, anxiety and depression in the family; improve their ability to cope and through structured competency based educational programmes will result in true partnership with parents. In this article we have discussed the historical perspective and recent evidence around FIC and compared this with FCC. We have also discussed the basic principles of FIC and then compared the various existing professional and parent focused neonatal care programmes and the advantages of FIC over those traditional models of care.